Carving Out a Space for Contemporary Dance in the South: Agnes Locsin's Continuing Legacy - Pison, Ruth Jordana Luna (Review of Women's Studies; Vol 21 No 1 (2011): Review of Women's Studies Volume XXI, Number 1 (January-June 2011))
This essay follows the trajectory of Locsin's choreographies as an artist initially based at the "center" of the arts in the Philippines, and later as an artist who decides to return to her home town in the South. One sees in the neo-ethnic and urbanative choreographies of Locsin how dance articulates the connections between milieu, motivations, and materials. While her neo-ethnic works resonate themes of nature, rituals, Asian arts, ethnic dances, and history, her urbanative choreographies are closer readings of what afflicts the Filipino of today, in particular the urban Filipino. Both the neo-ethnic and urbanative paths are proofs of Locsin's probing artistry; the two are not separate and distinct but intertwined paths. This essay likewise discusses various issues such as "cultural ownership" and "authenticity" which have surrounded the works of Locsin over the years. Ultimately, her choreographies point out to how dance is not only a language in which we write and re-write the past but is also an eloquent expression of the present.